IMPLEMENTING THE BRODY SCORING SYSTEM IN THE EVALUATION OF SEVERITY OF PULMONARY CHANGES IN CYSTIC FIBROSIS ON HIGH RESOLUTION COMPUTED TOMOGRAPHY - Nikolova, Sonja (My University, 2022)
This study aims to perform an in- depth assessment of the ubiquity and gravity of lung parenchymal changes in patients diagnosed with cystic fibrosis (CF) by implementing the Brody Scoring System (BSS) on High Resolution Computed Tomography (HRCT) exams. We analyzed and scored the HRCT scans of 11 patients diagnosed with cystic fibrosis with the mean age of 13, 5 (4 to 23 years old), by using the Brody Scoring System. All 11 patients underwent a HRCT according to appropriate diagnostic protocol on a 64- slice Somatom Definition AS+ Computed Tomograph (Siemens Healthineers, USA) on which we graded the findings of air trapping, peribronchial wall thickening, mucus plugging, bronchiectasis and most common parenchymal findings like ground glass opacities and consolidation, in peripheral and central locations in all 6 lobes of the lungs. Considering the habitual nature of the disease, bronchiectasis, mucus plugging and peribronchial wall thickening were the most consistent findings, whereas the others were less frequently encountered. The highest Brody score was affiliated with bronchiectasis and mucus plugging. There was a significant statistical difference between variables and predominant location only when mucus plugging and peripheral lung zones were in question and the common findings were more frequently located in the upper right lobe, followed by the lower lobes on both sides. High Resolution Computed Tomography has an important diagnostic role in the timely assessment of prevalence and severity of a spectrum of lung parenchymal changes in cystic fibrosis, whereas by using the readily available semi- quantitative scoring systems, gives an accurate estimation of the clinical status of the patients and predicts complications and unwanted outcomes.
Keywords: cystic fibrosis(CF); Brody Scoring System(BSS); High Resolution Computed Tomography(HRCT); air trapping; mucus plugging; bronchiectasis